2014
DOI: 10.1159/000354951
|View full text |Cite
|
Sign up to set email alerts
|

The Global Epidemic of Noncommunicable Disease: The Role of Early-Life Factors

Abstract: The rapid increase in prevalence of noncommunicable diseases (NCDs) is probably the most important global health problem of the 21st century. Already in every region except Africa, NCDs account for greater mortality than communicable, maternal, perinatal and nutritional conditions combined. Although modifiable lifestyle behaviors in adult life are the main risk factors, substantial evidence now suggests that factors in early life also have a major role in the development of NCDs. For instance, breastfeeding an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…A study from India that followed-up children between one and three, and five and seven years after an episode of SAM found that their mean WHZ was higher than their siblings who had not experienced malnutrition [ 21 ]. Whilst it is reassuring that complete or near-complete catch-up in WHZ is possible, there are potentially important life-course implications for these children as suggested by the accumulation of evidence on the Developmental Origins of Health and Disease (DOHAD) highlighting associations between rapid weight gain in infancy and later risk of non-communicable diseases (NCDs) [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study from India that followed-up children between one and three, and five and seven years after an episode of SAM found that their mean WHZ was higher than their siblings who had not experienced malnutrition [ 21 ]. Whilst it is reassuring that complete or near-complete catch-up in WHZ is possible, there are potentially important life-course implications for these children as suggested by the accumulation of evidence on the Developmental Origins of Health and Disease (DOHAD) highlighting associations between rapid weight gain in infancy and later risk of non-communicable diseases (NCDs) [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Critical time periods have been identified, both before conception and during fetal and postnatal development, where exposure to environmental factors, including altered nutrition, can cause adaptations to occur in the growing fetus and infant. 1,2 Although these effects may be adaptive in the short term, they may also be associated with adverse outcomes in childhood and later life, including a greater risk of obesity, 3 type 2 diabetes, heart disease 4-7 and allergy. 8 Significant contributions to this literature have been made by a number of long-term studies such as the British-based Avon Longitudinal Study of Parents and Children 9,10 and the Dutch-based Generation R Study.…”
mentioning
confidence: 99%
“…Defense against infectious disease is a matter of the highest importance for the health and development of children in developing countries. Breastfeeding is the most cost-effective intervention for protecting children against infectious diseases and all causes of mortality [4] . It is generally assumed that the protection is due to multiple anti-infective, anti-inflammatory, and immune regulatory factors transmitted through milk [5,6] .…”
Section: Background the Child Health Epidemiology Reference Group Of mentioning
confidence: 99%